Diseminasi Pertanian Ekologis di Desa Sangkanerang, Kecamatan Jalaksana, Kabupaten Kuningan - Dinda Emmy Gusti Sofhia; Riski Ramazayandi; Yayat Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The awareness of environmental cleanliness of the residents of Sangkanerang Village is still lacking, reflected in the habits of the villagers who throw their trash in the river including organic waste. Organic waste can be used for agricultural activities, such as fertilizer. Utilization of organic waste as fertilizer can be done by making vermicompost and MOL (Local Microorganisms). This activity aims to increase knowledge to the public about the use of organic waste, and to apply the principles of healthy agriculture in Sangkanerang Village. The method of this activity begins with a discussion with village officials, namely the Village Head and RW Chairperson. Information dissemination on activities carried out by each RW Chairperson will be submitted by the Sangkaneng Village community. The socialization activity was carried out with material presentation and demo on vermicompost and MOL. This event was followed by positive enthusiasm from the people of Sangkanerang Village. An indicator of success in this program is to provide understanding to the community that waste from harvesting and kitchen waste can be used as vermicompost and MOL. Vermicompost and MOL are relatively easy and inexpensive to be applied by the community, so people are interested in this fertilizer. Keywords: agriculture, organic waste, Sangkanerang village, MOL, vermicompost